2013
DOI: 10.1159/000345258
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Trigeminal Schwannoma: A Clinical Retrospective Study in 52 Cases

Abstract: Objective: To evaluate the radiological and clinical outcomes in a series of patients in whom stereotactic radiosurgery (SRS) was used to treat trigeminal schwannomas. Methods: The records of 52 patients who underwent SRS for trigeminal schwannoma were reviewed using a retrospective study. The median patient age was 47.1 years (range, 18-77); 20 patients (38.5%) had undergone prior tumor resection and 32 (61.5%) underwent radiosurgery on the basis of imaging diagnosis only. The most frequent presenting symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…32 Sun et al treated 52 patients with trigeminal schwannomas with radiosurgery using rotating gamma unit. 33 They reported a tumor control rate of 86.5% with near-total resolution in 15.4%, regression in 61.5%, unchanged tumor in 9.6%, and enlargement in 13.5% patients.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 94%
See 1 more Smart Citation
“…32 Sun et al treated 52 patients with trigeminal schwannomas with radiosurgery using rotating gamma unit. 33 They reported a tumor control rate of 86.5% with near-total resolution in 15.4%, regression in 61.5%, unchanged tumor in 9.6%, and enlargement in 13.5% patients.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 94%
“…32 In a study by Sun et al, the rate of improvement of presenting neurologic symptoms was 67.3%. 33 Radical surgical resection provides the best long-term control rate at the price of the highest incidence of neurologic deficits. Size obviously matters in terms of treatment strategies and often strongly influences the initial recommendation.…”
Section: Management Of Trigeminal Schwannomasmentioning
confidence: 99%
“…16,19,21 However, on average, the number of patients per study was 39, marginal dose was 14.5 Gy, tumor volume was 5.5 cm 3 , time to follow-up was 56 months, chance of clinical improvement was 48%, chance of tumor control was 91%, and chance of clinical worsening or new symptoms was 12% (most commonly trigeminal neuropathy/pain). 1, [14][15][16][17][18][19][20][21][22][23][24] Kano et al found that a higher marginal dose was correlated with improved tumor control. 1 Snyder et al found that a higher marginal dose was associated with increased rates of tumor expansion.…”
Section: Review Of Stereotactic Radiosurgery For Trigeminal Schwannomasmentioning
confidence: 99%
“…Management strategies for TS include observation (in incidentally discovered tumors), partial or complete microsurgical resection, [3][4][5][6][7][8][9][10][11][12][13] or stereotactic radiosurgery (SRS). 1,[14][15][16][17][18][19][20][21][22][23][24] Initial microsurgical resection is necessary for larger volume tumors causing symptomatic brainstem compression. SRS is a primary management strategy for smaller volume tumors and as an adjuvant salvage option after attempted resection of larger tumors associated with symptomatic mass effect.…”
Section: Introductionmentioning
confidence: 99%
“…1 These tumors of the skull base account for 0.07 to 0.36% of intracranial tumors and 1 to 8% of adult intracranial schwannomas, but they can make up around 10% of schwannomas encountered in adolescence. [2][3][4][5][6] This correlates to an approximate incidence of 1 case per 100,000 inhabitants, affecting predominantly women between the fourth and sixth decade of life. Malignant TS are very infrequently reported and mainly occur associated with neurofibromatosis type 1.…”
Section: Introductionmentioning
confidence: 99%